Adaptive time-delay estimation based on normalized maximum correntropy criterion for near-field electromagnetic ranging. (April 2018) - Luo, Yuanzhe; Sun, Guolu; Zhang, Xiaotong; Wang, Peng; Liu, Tianxin; Xu, Gang
Highlights: By exploring the time-delay estimation issue instead of the phase difference between the electronic and magnetic components of low-frequency signals, we improve the accuracy of near-field ranging. When encountering impulsive noise, correntropy can perform better than the traditional adaptive algorithms. The NMCC-ATDE algorithm can avoid a sudden increase in input power effectively, which ensures more stable performance in time-delay estimation. Abstract: Indoor location systems can track objects using near-field electromagnetic ranging technology (NFER). However, the ranging error can be large because the phase difference between the electronic and magnetic fields cannot be measured directly. This study proposes a method that adopts an adaptive time-delay estimation algorithm based on a normalized maximum correntropy criterion (NMCC-ATDE) instead of exploiting the phase behavior of the electromagnetic signal for near-field ranging. In the NMCC-ATDE algorithm, the input signal is normalized to mitigate any sudden increase in the input signal. As our simulation results reveal, compared to the algorithms based on maximum correntropy criterion and normalized least mean square, the NMCC-ATDE algorithm can estimate the time delay in real time with a fast convergence rate and small steady-state error. Graphical abstract: Image, graphical abstract